Respuesta :
Answer:
Q1: 2-y/4+y
- 2-2/4+2
- 2+2-1/2
- 4-1/2
- (8-1)/2
- 7/2
Q2: 3 (y+2)/y
- 3(2+2)/2
- 3×4/2
- 3×2
- 6
By putting the given value in the algebraic expressions, the expressions become 5.5 and 6.
What is algebraic expression?
An algebraic expression in mathematics is an expression which is made up of variables and constants, along with algebraic operations.
[tex]=2 - \frac{y}{4} +4\\ \\= 2 - \frac{1}{2} +4\\ \\= \frac{11}{2} \\\\\\=\frac{3(y+2)}{y} \\\\=\frac{3*4}{2}\\ \\=6[/tex]
Learn more about algebraic expression here
https://brainly.com/question/953809
#SPJ3